Extension Phenomena for Holomorphic Geometric Structures - McKay, B. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
The most commonly encountered types of complex analytic G-structures and Cartan geometries cannot have singularities of complex codimension 2 or more.